Clinical applications of optical coherence tomography (OCT) in glaucoma - Saheb, Hady; Salimi, Ali (Canadian Eye Care Today, 2022)
Visual field (VF) testing has been the mainstay for diagnosing and monitoring glaucoma. However, relying solely on VF can delay the patient’s diagnosis in the early stages of the disease, as the structural changes are known to precede the functional changes and VF defects may not be clinically detectable until at least 25-35% of retinal ganglion cells (RGCs) are lost. This concept highlights the importance of alternative diagnostic modalities such as optical coherence tomography (OCT). OCT’s ability to reliably segregate and quantify the thickness of retinal layers has allowed earlier detection of glaucoma, up to 6 years before the onset of any detectable VF loss. Compared to VF, OCT is less time-consuming and is less dependent on the patient’s cooperation and test-taking ability. There are a few commercially available spectral domain OCT (SD-OCT) machines that are routinely used in glaucoma clinics. These devices are fundamentally similar with comparable performance, but their scanning protocols and segmentation algorithms are not analogous; thus, the measured parameters may not necessarily be interchangeable between devices and the values should be interpreted relative to the normative databases specific to each machine. In this review, we present the clinical applications of OCT imaging in glaucoma and share some clinical pearls and pitfalls.